Pangsa Pasar dan Permintaan Kopi Robusta Indonesia di Jepang - Budiarto Budiarto; Sri Widodo; Masyhuri Masyhuri; Dwidjono Haji Darwanto (Jurnal Dinamika Sosial Ekonomi, 2004)
This research aims to analyze: 1), market share of Indonesian robusta coffee in Japan markets, 2). dynamic demand of Indonesian robusta coffee in Japan markets. The data is time series secondary of 1981-2001. The analysis is using econometric analysis of double log linear regression model with Ordinary Least Square (OLS) and Autocorrelation. The result of analysis indicate that market share have a comparative advantage, this indexes of Revealed Comparative > 1,00. Demand of Indonesian robusta coffee responsive to price of Indonesian robusta in international markets, price of arabica coffee in Japan markets and market share of Indonesian robusta coffee in Japan markets.Key words: market share, coffee price, dynamic demand